The Influence of Co-branding, Fear of Missing Out (FoMO), and Brand Personality on Brand Preference and Purchase Intention - Belinda Putri Widyaningrum; Helma Malini; Erna Listiana; Barkah Barkah; Ana Fitriana (eCo-Buss, 2025)
Indonesia unresolved plastic waste problem has led to the emergence of more environmentally friendly products innovations, such as tumbler. One of the currently popular tumblers is Corkcicle, which is known for its quality and often collaborates with well-known brands. This study aims to understand how co-branding, FoMO, and brand personality jointly influence consumer purchase intention towards Corkcicle products. Brand preference is assumed to be a mediating variable, meaning that these three independent factors first influence brand preference, which then has an impact on consumers purchase intention. A quantitative methodology was employed, gathering data through questionnaires distributed to 220 qualified respondents. The analysis utilized Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS v.4 software to evaluate the hypotheses based on the responses collected. Findings reveal that co-branding, FOMO, and brand personality have a significant effect on both brand preference and purchase intention for Corkcicle products, with co-branding exerting the most substantial influence.